Characteristic of Swamp Buffalo (Bubalus Bubalis) Pampangan at Ogan Komering Ilir, South Sumatera, Indonesia - Windusari, Yuanita; Hanum, Laila; Nofyan, Erwin; Kamal, Mustafa; Amsar, Adri (Animal Review, 2016)
The aim of research to study the character and analyze the phenotypic diversity among variants swamp buffalo (Bubalus bubalis) Pampangan at Ogan Komering Ilir, South Sumatera. Quantitative data are determined by the circumference of the chest (Li Da), body length (Pa Ba), tail length (Pa Ek), the length of the head (Pa Ke), head width (Le Ke) and hip height (Ti Pi). Qualitative data is determined based on the character of each variant shown through the hair color, the shape and direction of growth of the horn. Characteristics that indicate of genetic relationship between the variant of swamp buffalo. Methods of observations carried out directly on the morphology and methods NTSYS Ver. 2.1 to the analysis of kinship and then presented in the form of a dendrogram. Results showed that there are four variants of buffalo Pampangan namely red buffalo, black buffalo, buffalo striped and Lampung buffalo. Morphology of buffalo such as body size, hair color, shape and direction of growth of the horns is different. Genetic relationship shown with value of correlation coefficient 0.57 was found in group A (OTU-1) and group B (OTU-2, OTU-3 and OTU-4), and value of correlation coefficient 0.612 found in group A (OTU-2 and OTU-4) and group B (OTU-3). The correlation coefficient of more than 0.57 indicates a kinship between the variance of the swamp buffalo Pampangan relatively close. It is suspected inbreeding between variants tends to be high. The analysis also showed that the closest genetic relationships found in OTU-2 (black buffalo) and OTU-4 (buffalo Lampung) with a correlation coefficient 0.85. This condition is believed that the OTU-2 and OTU-4 derived from the same lineage.